Bifidobacterium breve during infancy attenuates mobility in low birthweight rats. Issue 1 (8th August 2022) - Itoh, Ayaka; Tanaka, Nao; Fukunaga, Sachiko; Nakano‐Doi, Akiko; Matsuyama, Tomohiro; Nakagomi, Takayuki; Tsuji, Masahiro
Abstract: Background: Children with low birthweight (LBW) have a higher risk for developing attention‐deficit/hyperactivity disorder, for which no prophylactic measure exists. The gut microbiota in infants with LBW is different from that in infants with normal birthweight and is associated with attention‐deficit/hyperactivity disorder. Oral supplementation with Bifidobacterium has several health benefits, such as suppressing inflammation. Methods: We examined the effect of gavage supplementation with Bifidobacterium breve M‐16V from postnatal days 1–21 in a rat model of intrauterine hypoperfusion. Results: The open‐field test at 5 weeks of age (equivalent to human pubertal age) showed that rats in the LBW‐vehicle group were marginally hyperactive compared with rats in the sham group, while rats in the LBW‐B.breve group were significantly hypoactive compared with rats in the LBW‐vehicle group. The gut microbiota in the LBW‐vehicle group exhibited a profile significantly different from that in the sham group, whereas the gut microbiota in the LBW‐B.breve group did not exhibit a significant difference from that in the sham group. Anatomical/histological evaluation at 6 weeks of age demonstrated that the brain weight and the cerebral areas on coronal sections were reduced in the LBW groups compared with the sham group. Probiotic supplementation did not ameliorate these morphological brain anomalies in LBW animals. The percentage of Iba‐1 + cells in the brain was not different among the LBW‐B.breve, LBW‐vehicle, and sham groups. Conclusion: Bifidobacterium breve supplementation during early life is suggested to have the potential to help children with LBW attenuate hypermobility in adolescence.